Antidiabetic characterization and mechanism of action of wogonin in rats - Ahmed, Qamar Uddin; Mat So'ad, Siti Zaiton; Bakhtiar, Muhammad Taher; Sarian, Murni Nazira; Alhassan, Alhassan Muhammad; Afrin, Mehnaz; Hasan, Md. Mahmudul (Stu); Latip, Jalifah (2018)
This research deals with the in vivo, in vitro, and in situ evaluations of antidiabetic effect of wogonin to understand its mechanism of action as an antdiabetic agent. Wogonin was isolated from the leaves extracts of T. indica. Its thirteen chemical analogues (including semisynthetic derivatives) were also taken into account for structure activity relationship study and their structures were characterized by IR, UV, 1D and 2D NMR and MS spectral analysis. The results of animal study, cell culture antidiabetic (insulin secretion, adipogenesis, glucose uptake), and protein expression showed that the methyl ether group at position C-8 is responsible for wogonin’s antidiabetic property via β-cells of islet of langerhans’ recovery as well as through glucose uptake mechanism which indicated by up regulation of GLUT 4 and C/EBP-α. The mechanism could be enhanced by the addition of acetate group at C-5 and C-7. SAR study revealed that the total number and the configuration of hydroxyl groups play a vital role in regulating antidiabetic and antioxidant activities. Presence of C-2-C-3 double bond and C-4 ketonic group were found to be two essential structural features in the bioactivity of wogonin especially for antidiabetic property. For in situ experiments, the molecular docking study, quercetin showed the highest score among the chemical analogues of wogonin revealing the importance of hydroxyl groups. Results conclude that wogonin exerts antidiabetic effect through different mechanisms of action. In vivo study, it displayed antidiabetic effect through regenerating beta cells of pancreas, thereby found to increase the level of insulin in body. However, in vitro experiments, it showed effect like insulin and rosiglitazone by inducing adipogenesis and glucose uptake. It also showed α-glucosidase, dipeptyl peptidase-4 inhibitory effects, however, at high concentration. In vivo and in vitro results demonstrate that wogonin may exert its antidiabetic effect through multiple modes of action. SAR study showed that by removing its methoxy group and through addition of hydroxyl groups to the different positions of wogonin could increase its antidiabetic effect and decrease its toxicity.